Μελέτη του συστήματος ελέγχου κίνησης και της προστασίας έναντι της οξείδωσης της κατεργαζόμενης περιοχής σε πρωτότυπη μηχανή SLS/SM - Ιάσων, Σιδέρης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Τεχνολογίας των Κατεργασιών, 2018)
The scope of this thesis is the evolution of the existing control schemes found in the prototype SLS/SLM machine (Selective Laser Sintering { Melting ) of the Manufacturing Technology Laboratory at the School of Mechanical Engineering of NTU of Athens and the design of an innovative apparatus for local chamber insulation. The aim of the study is to create a high precision machine, with the capability of controlling manufacturing parameters and fully harness the advantages of this additive manufacturing technique. The rst subject developed is the design of a robust and precise control scheme driving the movement of the laser head. After proving that controlling each axis separately does not provide su cient accuracy in tracking, three cross-coupled control schemes were tested in both transient and steady state responses for linear and non-linear paths. Selection was based in criteria of response quality. Next in order, is the exploration of an adaptive control architecture used for on-line manipulation of powder temperature. After investigating the physical aspects and the possible solutions concerning this matter, an adaptive scheme is proposed based on the existing equipment of our lab. Finally, we proceeded in the research for means of locally insulating the SLS-SLM machine, by creating an apparatus fastened to laser head. A ventilation system attached to the apparatus prohibits oxygen entering the chamber.